2018
DOI: 10.1038/s41598-018-31891-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved fragment-based protein structure prediction by redesign of search heuristics

Abstract: Difficulty in sampling large and complex conformational spaces remains a key limitation in fragment-based de novo prediction of protein structure. Our previous work has shown that even for small-to-medium-sized proteins, some current methods inadequately sample alternative structures. We have developed two new conformational sampling techniques, one employing a bilevel optimisation framework and the other employing iterated local search. We combine strategies of forced structural perturbation (where some fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…The only difference between 'standard' Rosetta predictions and SS-Rosetta is that instead of relying on 25 9-mers and 200 3-mers, which are the default numbers of fragments that have adopted by Rosetta for more than 15 years [72,99,100], SS-Rosetta customises them according to the target. Whilst the whole fragment selection process has not been altered, the number of fragments at specific positions is changed.…”
Section: Experiments and Datasetmentioning
confidence: 99%
“…The only difference between 'standard' Rosetta predictions and SS-Rosetta is that instead of relying on 25 9-mers and 200 3-mers, which are the default numbers of fragments that have adopted by Rosetta for more than 15 years [72,99,100], SS-Rosetta customises them according to the target. Whilst the whole fragment selection process has not been altered, the number of fragments at specific positions is changed.…”
Section: Experiments and Datasetmentioning
confidence: 99%
“…In a previous study [5], we introduced two new sampling protocols designed to realise more extensive exploration of the available set of conformations within individual runs (a brief description of the methods appears in Section 1.2). We demonstrated that when good fragment sets are used, this improved exploration can translate into more frequent and reliable sampling of near-native basins in the energy landscape for many targets.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], our experiments using older and newer fragment sets suggested that the fragment sets and choice of sampling algorithm do both play important roles. To address the first of the above questions, it is valuable to investigate the rate at which native-like local minima are accessed during runs of our protocols.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations